2020
DOI: 10.1002/jcph.1789
|View full text |Cite
|
Sign up to set email alerts
|

Application of Microdosed Intravenous Omeprazole to Determine Hepatic CYP2C19 Activity

Abstract: Omeprazole is an established probe drug to assess cytochrome P450 (CYP) 2C19 activity (phenotyping). Because it has nonlinear pharmacokinetics (PK) after oral administration (autoinhibition of metabolism), the true impact of coadministered perpetrators on CYP2C19 substrates might be underestimated after regular doses. We tested the dose linearity of an intravenous omeprazole microdose of 100 μg and compared it with a 20-mg dose in 4 healthy poor metabolizers (PMs) and 6 extensive metabolizers (EMs) of CYP2C19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The amount of sodium bicarbonate administered with omeprazole seems to be important for absorption. Park and co-workers administered 10 mmol of sodium bicarbonate resulting in a relative bioavailability (F rel ) of 0.35 of the microdose [ 13 ]. Bioequivalence studies showed that uncoated omeprazole in combination with 48 mmol sodium bicarbonate was bioequivalent to an encapsulated formulation [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The amount of sodium bicarbonate administered with omeprazole seems to be important for absorption. Park and co-workers administered 10 mmol of sodium bicarbonate resulting in a relative bioavailability (F rel ) of 0.35 of the microdose [ 13 ]. Bioequivalence studies showed that uncoated omeprazole in combination with 48 mmol sodium bicarbonate was bioequivalent to an encapsulated formulation [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…All participants had a known CYP2C19 genotype previously determined in a genotyping study where common cytochrome isozyme polymorphisms were examined. CYP2C19 genotyping was performed for CYP2C19*2 (rs4244285), CYP2C19*3 (rs4986893), and for CYP2C19*17 (rs12248560) as previously described [ 13 ] and the presence of two wild type alleles was assumed if none of the tested polymorphisms was present.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations